Syngas Production from Methane Dry Reforming Over Ni/Al2O3 Catalyst - Vo, Dai-Viet N.; Selvarajah, Kavineshshen; Nguyen, Huu Huy Phuc; Abdullah, Bawadi; Alenazey, Feraih (Springer, 2016)
We evaluated dry reforming of methane in a tubular fixed-bed reactor at various reaction temperatures from 923 to 973 K using different reactant compositions over 10 % Ni/Al2O3 catalyst prepared by a wet impregnation method. Both NiO and NiAl2O4 phases were formed on the catalyst surface during calcination, and the 10 % Ni/Al2O3 catalyst possessed high surface area of 106.36 m2 g-1 with fine metal dispersion. The low activation energy observed for formation of NiAl2O4 phase during calcination indicated strong interaction between the NiO form and the c-Al2O3 support. The NiO phase was completely reduced to metallic Ni0 form via H2 reduction. The conversions of CO2 and CH4 increased noticeably with increasing CO2 partial pressure, and the H2/CO ratio was always below unity, regardless of reaction conditions. The yield of H2 was enhanced with growing CO2 partial pressure, approaching a highest value of about 70 %. The heterogeneous nature of the deposited carbon was evident from the coexistence of carbon nanofibers and graphitic carbon. In addition, the amount of filamentous carbon appeared to be slightly less than that of graphitic carbon. However, these deposited carbons were completely removed by O2 at below 900 K during temperature-programmed oxidation.